Granzyme A Produced by γ9δ2 T Cells Activates ER Stress Responses and ATP Production, and Protects Against Intracellular Mycobacterial Replication Independent of Enzymatic Activity - Rasi, Valerio; Wood, David C.; Eickhoff, Christopher S.; Xia, Mei; Pozzi, Nicola; Edwards, Rachel L.; Walch, Michael; Bovenschen, Niels; Hoft, Daniel F. (Frontiers in Immunology, 2021)
Mycobacterium tuberculosis (Mtb), the pathological agent that causes tuberculosis (TB) is the number one infectious killer worldwide with one fourth of the world’s population currently infected. Data indicate that γ9δ2 T cells secrete Granzyme A (GzmA) in the extracellular space triggering the infected monocyte to inhibit growth of intracellular mycobacteria. Accordingly, deletion of GZMA from γ9δ2 T cells reverses their inhibitory capacity. Through mechanistic studies, GzmA’s action was investigated in monocytes from human PBMCs. The use of recombinant human GzmA expressed in a mammalian system induced inhibition of intracellular mycobacteria to the same degree as previous human native protein findings. Our data indicate that GzmA is internalized within infected cells and that the active site is not required to inhibit intracellular replication of mycobacteria. Global proteomic experiments demonstrated that the ER stress response and ATP producing proteins were upregulated after GzmA treatment, and these proteins were confirmed by examining their expression in an independent set of patient samples. Our data suggest that immunotherapeutic host interventions of these pathways may contribute to better control of the current TB epidemic.